PENGUATAN MEDIA INTERNAL PONDOK PESANTREN DENGAN PELATIHAN FOTOGRAFI JURNALISTIK - Fani Nur Jannah; Cecep Gunawan; Fitri Nur Ardiantika; Tan Sri Zulfikar (Universitas Negeri Surabaya, 2026)
This community service program aimed to enhance journalistic photography skills among the teachers, administrators, and students of Pondok Pesantren Uzlifatil Jannah through a structured training program. The activity was motivated by the crucial role of the pesantren’s internal media in delivering factual, authentic, and engaging visual information, despite the participants’ limited technical ability and lack of understanding of journalistic photography ethics. The training method combined theoretical sessions, demonstrations of photographic techniques, and hands-on practice in documenting pesantren activities. The training materials covered the fundamentals of photojournalism, including its functions and requirements, various types of journalistic photographs (spot photos, general news photos, people in the news, daily life photos), as well as technical aspects such as camera angles, framing, composition (rule of thirds and leading lines), and the development of a photo essay. Evaluation was conducted through pretest and posttest assessments to measure participants’ improvement in knowledge and practical skills. The results indicated a significant improvement in participants’ performance, with the average score increasing from 58.0 in the pretest to 77.5 in the posttest. The standard deviation also decreased from 11.69 to 2.38, suggesting a more uniform skill acquisition among participants after the training. Furthermore, the participants’ responses reflected notable progress in knowledge, motivation, readiness, and practical ability. In conclusion, this training successfully enhanced the participants’ capacity to produce photographs that adhere to journalistic principles and ethics. The program is expected to strengthen the role of the pesantren’s internal media as a professional platform for da’wah, education, and publication.